Effectiveness of the “Hand as Foot” teaching method in human physiology: A randomized controlled trial - Ya-Na Su; Ding-Yun Zhao (Asian Journal of Surgery, 2024)
Background: The ''Hand as Foot'' teaching method, an innovative approach in medical education, utilizes hand gestures to simulate anatomical structures and functions. This study aimed to assess the effectiveness of the ''Hand as Foot'' teaching method compared to traditional method in the ''Human Physiology'' course. Methods: During the 2023 spring semester, a randomized controlled trial involved 84 health management students. Participants were randomly assigned to the ''Hand as Foot” teaching group or the traditional teaching group. A self-designed Likert scale was used to evaluate students' perceptions of teaching effectiveness, covering dimensions such as engagingness, intuitiveness, facilitation of understanding, enhancement of memorization, and effortlessness of learning. Additionally, a knowledge assessment test was administered to measure knowledge acquisition. Results: The ''Hand as Foot teaching method'' group (41 students) reported significantly higher ratings for all dimensions of teaching effectiveness compared to the traditional teaching group (43 students) (p ≤ 0.01). Despite the lack of statistical significance, the experimental group's test scores were notably superior (Mean = 6.35 vs. Mean = 5.94). Discussion: The ''Hand as Foot'' teaching method demonstrated superior effectiveness in engaging students, facilitating comprehension, and enhancing memorization. Its interactive and tangible nature provided a holistic learning experience, enabling students to visualize complex physiological mechanisms. Additionally, it fostered active student participation and a desire for deeper understanding. Conclusion: While the ''Hand as Foot'' teaching method demonstrated strengths in engaging students and aiding comprehension, further researches with larger and diverse cohorts are needed to gauge its impact on learning outcomes and broader applicability.